The Concept of Imamate and the Theory of Wilayatul Faqih in the Islamic Republic of Iran: الإمامة ونظرية ولاية الفقيه في جمهورية إيران الإسلامية - Abdul Haris (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Al-Qur’an and Hadith the two main sources of Islamic teaching do not mention any kind of state that moslems should build whether it be monarchy state or democratic one. More than that, both sources do not either tell the way to choose a leader. Al-Qur’an only tells that the public affairs should be discussed among the moslems particularly their prominent figures. So it was the creativity and improvisation of the disciples of the late prophet when they chose the first four caliphs. On the other hand, the Syiah community established their belief that leadership (imamah) of moslems community does not belong to any moslem but it belongs to Ali Bin Abi Thalib and his descendants. Then the imamah transformed to the concept of Wilayatul Faqih in the modern Islamic Republic of Iran. This study describes how the concept of imamah growed and transformed to theory of wilayatul faqih in Syiah community of Iran